Jornalismo, sociedade e crítica - potencialidades e transformações - Coelho, Diônatas Álisson (Universidade do Vale do Rio dos Sinos, 2015)
This dissertation is dedicated to understanding the relations between the social comments about the media and the development of the current journalism. It starts with the idea that the circulation of comments in the society, especially through the internet, with a critical component in relation to the products of journalism may be causing tension and changes of practices in the newsrooms. The possibility in question is that comments have the potential to generate a new way of thinking about practices used in the mass media. The aim is to understand how the comments are received, selected and moved through the newsrooms of Brazilian newspapers, and finally which affectations they generate in the development of the news. The current analysis is based on the discussion of the changes in the society and communication particularly since the internet popularization. This observation rethinks the reader position in this context discussing its role as a passive receiver and as a reader who assesses and produces along with the media. A discussion about the possibilities of this relation and the results of what José Luiz Braga (2006) calls Social Response System is created in order to observe the critical work undertaken by these people. The discussion is enhanced by the observations taken through exploratory researches performed in the newspapers O Globo, in October 2013, Correio Braziliense, in November 2013, Folha de São Paulo, in October 2014, and Zero Hora, in November 2014. Editors were interviewed in the newsrooms and the routines of interaction between the social comments and the newspapers were observed. At this moment, it is postulated that the contact has generated affectations in the journalistic practices which come from the conscience of having a more alert society. From a theorerical point of view, we believe this moment may generate another way of thinking about the theories involving the elements that act in the construction of the news. In this context, the research looks for a theoretical basis which outlines the social criticism flows in the newsrooms, its limitations and potentialities.
Keywords: Jornalismo; Crítica midiática; Sociedade; Construção da notícia; Redes sociais; Journalism; Media critics; Society; Development of news; Social networks; ACCNPQ::Ciências Sociais Aplicadas::Comunicação